Estrategias de gestión de talento humano y su incidencia en la calidad del servicio del Gad municipal de Mocache, año 2023 - Coello Pacheco, Georgina Selena (2025)
This research analyzed how human talent management strategies influence the quality of services at the Mocache Municipal Government (GAD) during 2023. The descriptive study used surveys of 151 employees and 378 citizens over the age of 18, an interview with the human resources director, and a comparative analysis of training programs between 2022 and 2023. The findings revealed that the institution implemented internal reorganization, training, and performance evaluations, achieving improvements in job definition and the work environment. However, weaknesses were detected in the measurement of results, unequal development opportunities